ACTUAL PROBLEMS MANAGEMENT COMMUNICATION: PSYCHOLOGICAL CONTEXT - Cherusheva, Halyna; Parkhomenko, Viktoriya (Sworld-Us Conference proceedings, 2022)
At the present stage of Ukraine's development, priority attention is paid to the training of a new generation of highly qualified managerial personnel with non-standard thinking, who are able to master the social and ideological paradigm of national state